The New Exchange Rate Policy in the Emerging Market Economies: with Special Emphasis on China - Friedrich L. Sell (Universität der Bundeswehr München, Fachgruppe für Volkswirtschaftslehre, 2006)
In this paper, we discuss the new aspects of exchange rate policy which can be observed in the emerging market economies and their most likely implications for allocation, distribution and stabilization goals. A special emphasis is put on the Chinese case, where large interventions in the foreign exchange market point at a significant undervaluation of the Renminbi. With many alternatives at choice, Chinese authorities still prefer to peg their currency, by and large, to the US-Dollar. On July 21, 2005 a moderate revaluation and the introduction of a basket peg was announced, but a basket peg strategy is not yet visible in empirical figures. On the background of Germany's experiences of 1969, almost on the eve of the Bretton Woods' system collapse, we model a speculative attack on an undervalued currency in the vein of the Flood-Garber seminal paper from 1984. The contents of the model are reflected against today's reality in China, but also against Germany's experiences in the past century. We come to the conclusion, quite in line with Germany's experience of 1969, that the monetary authorities in China should anticipate such an attack and quickly proceed to a revaluation of the Renminbi. We then propose a sequence of reforms/policies which should be implemented in the aftermath.
Keywords: O23; E58; F31; 330; Absorption Emerging markets economies; exchange rate policy; speculative attack; first generation models